1997
DOI: 10.1002/marc.1997.030181211
|View full text |Cite
|
Sign up to set email alerts
|

Cationic initiation of oligomerization of vinylformamide

Abstract: Vinylformamide (VFA) is cationically polymerized in various solvents at 273 K and reaction temperature by the following initiators: iodine, bis(4‐methoxyphenyl)‐methyl chloride/silica, triphenylmethyl chloride/silica, and trimethylsilyl triflate. In every case defined oligomers with narrow molecular weight distribution are obtained in moderate yield (20–50%). Acid hydrolysis of the obtained oligomers yields well defined oligovinylamine products. The cationic initiation mechanism of VFA is discussed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 5 publications
0
31
0
1
Order By: Relevance
“…A combination of both processes is advantageous because the hydrolytically unstable Si1O1C -linkages are shielded by crosslinked polymer [20][21][22] . In a previous paper we reported that it is possible to polymerize cationically vinylformamide (VFA) by arylmethyl halides supported on a silica gel surface or by iodine 23) . In spite of the presence of the basic oxygen and nitrogen atoms of the monomer, the formation of C1C linked oligomers is observed.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of both processes is advantageous because the hydrolytically unstable Si1O1C -linkages are shielded by crosslinked polymer [20][21][22] . In a previous paper we reported that it is possible to polymerize cationically vinylformamide (VFA) by arylmethyl halides supported on a silica gel surface or by iodine 23) . In spite of the presence of the basic oxygen and nitrogen atoms of the monomer, the formation of C1C linked oligomers is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Warunkiem formowania ³añcucha polimeru w polimeryzacji jonowej jest atak elektrofilowy tylko w kierunku "a". Zatem mo¿liwooeae ataku w pozosta³ych dwóch kierunkach ("b" i "c") prowadzi do utworzenia wy³¹cznie krótkich ³añcuchów i licznych niepo¿¹danych produktów ubocznych [12,[18][19][20]. W polimeryzacji rodnikowej NVF uzyskiwane ciê¿ary cz¹steczkowe tak¿e nie s¹ zbyt du¿e i nie dorównuj¹ wartooeciom jakie mo¿na otrzymaae polimeryzuj¹c akryloamid.…”
Section: Nvf R1unclassified
“…More recent and more extensive work by Spange et al [74] involved the investigation of cationic polymerisation of VFA with other initiators, e.g. iodine, triphenylmethyl chloride/silica gel, trimethylsilyl triflate and oligomers.…”
Section: Chmentioning
confidence: 99%